Proteomic profile of candida albicans biofilm - Abdulghani, Mazen; Iram, Rasiqua; Chidrawar, Priti; Bhosle, Kajal; Kazi, Rubina; Patil, Rajendra; Kharat, Kiran; Zore, Gajanan (Journal of Proteomics, 2022)
Candida albicans biofilms are characterized by structural and cellular heterogeneity that confers antifungal resistance and immune evasion. Despite this, biofilm formation remains poorly understood. In this study, we used proteomic analysis to understand biofilm formation in C. albicans related to morphophysiological and architectural features. LC-MS/MS analysis revealed that 64 proteins were significantly modulated, of which 31 were upregulated and 33 were downregulated. The results indicate that metabolism (25 proteins), gene expression (13 proteins), stress response (7 proteins), and cell wall (5 proteins) composition are modulated. The rate of oxidative phosphorylation (OxPhos) and biosynthesis of UDP-N-acetylglucosamine, vitamin B6, and thiamine increased, while the rate of methionine biosynthesis decreased. There was a significant modification of the cell wall architecture due to higher levels of Sun41, Pir1 and Csh1 and increased glycosylation of proteins. It was observed that C. albicans induces hyphal growth by upregulating the expression of genes involved in cAMP-PKA and MAPK pathways. This study is significant in that it suggests an increase in OxPhos and alteration of cell wall architecture that could be contributing to the recalcitrance of C. albicans cells growing in biofilms. Nevertheless, a deeper investigation is needed to explore it further.Significance: Candida sps is included in the list of pathogens with potential drug resistance threat due to the increased frequency especially colonization of medical devices, and tissues among the patients, in recent years. Significance of our study is that we are reporting traits like modulation in cell wall composition, amino acid and vitamin biosynthesis and importantly energy generation (OxPhos) etc. These traits could be conferring antifungal resistance, host immune evasion etc. and thus survival, in addition to facilitating biofilm formation. These findings are expected to prime the further studies on devising potent strategy against biofilm growth among the patients.
Keywords: Biofilm; Candida albicans; Cell wall; LC-MS; Metabolism; MS; proteomics